Design of multi-parametric NCO tracking controllers for linear dynamic systems. (2nd September 2016) - Sun, Muxin; Chachuat, Benoît; Pistikopoulos, Efstratios N.
Abstract : Highlights: A methodology for combining multi-parametric programming and NCO tracking is proposed. The multi-parametric switching structure of constrained linear-quadratic optimal control problems is characterized. The feedback law in a given critical region is time-varying and potentially nonlinear in the uncertain parameters. The resulting mp-NCO-tracking controllers lead to a large reduction in the number of critical regions. Abstract: A methodology for combining multi-parametric programming and NCO tracking is presented in the case of linear dynamic systems. The resulting parametric controllers consist of (potentially nonlinear) feedback laws for tracking optimality conditions by exploiting the underlying optimal control switching structure. Compared to the classical multi-parametric MPC controller, this approach leads to a reduction in the number of critical regions. It calls for the solution of more difficult parametric optimization problems with linear differential equations embedded, whose critical regions are potentially nonconvex. Examples of constrained linear quadratic optimal control problems with parametric uncertainty are presented to illustrate the approach.